Coping Strategies and Sense of Care Among Parents of Children Affected by Sturge–Weber Syndrome: A Cross-Sectional Study. - de Benito Alberto, Hernández; Toro María Isabel, Buceta; Guijo María, Sanz; Gallardo María Pilar, Serrano (Nursing Reports, 2026)
Background/Objectives: The diagnosis of a rare disease such as Sturge–Weber syndrome (SWS) has a profound emotional impact on parents, who must adapt to an unexpected and complex caregiving role. This study aimed to analyse the sense of caregiving among parents of children with SWS and to identify the coping strategies they adopt. Methods: A cross-sectional descriptive study was conducted with 28 parents of children with SWS in Spain. Data were collected using the Brief COPE inventory and the Finding Meaning Through Caregiving Scale (FMTCS). Descriptive statistics and non-parametric bivariate analyses were performed. Results: Acceptance (mean = 5.14; SD = 0.85) and active coping (mean = 5.07; SD = 1.12) were the most frequently used coping strategies. Higher provisional meaning in caregiving was positively associated with active coping (ρ = 0.423; p = 0.025), acceptance (ρ = 0.562; p = 0.002), and humor (ρ = 0.557; p = 0.002). As children aged, parents reported a greater sense of caregiving meaning (ρ = 0.294; p = 0.049). Conclusions: Parents of children with SWS tend to adopt active and adaptive coping strategies over time, finding increasing meaning in their caregiving role. These findings highlight the importance of nursing-led interventions aimed at supporting parental coping, meaning-making, and emotional well-being in families affected by rare diseases.